Screening for potential embryotoxicity of phytochemicals and gestational diabetes mellitus using the chick cardiomyocyte micromass system and stem cell differentiation: prediction by molecular targets - Mohammed, Omar Jasim Mohammed (2017)
Congenital heart defects are a leading cause of postnatal loss; they could genetically or environmentally induced. Herbal remedies are often used during the early stages of pregnancy, being considered ‘harmless’ and ‘natural'. To alleviate pregnancy-induced symptoms, women frequently use herbal medicines such as ginger to relieve nausea and vomiting - ‘morning sickness’, gingko biloba and ginseng as dietary supplements or tonics to boost body energy and blood circulation, particularly to the brain. Also, chamomile and holy basil are recommended to promote calmness and reduce stress, often related to planned or unplanned pregnancy. These easily available and accessible medicinal herbs could be possible causes of congenital malformations. Additionally, diabetes mellitus in gestation is a considerable medical challenge, since it is related to ‎augmented dangerous morbidity and mortality for both the fetus ‎and the pregnant woman. Two in vitro methods were utilised; chick embryonic heart micromass (MM) and mouse embryonic D3 stem cells (ESD3). The potential effects of the tested herbal components in both in vitro systems were evaluated by monitoring the alteration in several endpoints. These include contractile activity (morphological scoring system), cell activity, total protein content, ROS production, DNA damage, transmembrane proteins expression (connexin43, integrin β1) and stem cell migration. In MM, 6-gingerol decreased contractility, cell activity and protein content. It caused an increase in ROS production and DNA damage and a decrease in transmembrane protein expression (connexin43, integrin β1) at high concentrations. In ESD3, 6-gingerol severely affected differentiation into cardiomyocytes cell activity and protein content at both low and high concentrations. With regards to ginkgolide A and ginkgolide B, there were alterations for few endpoints in both systems at moderate to high concentrations. G-Rg1, from ginseng, decreased contractile activity, cell activity, protein content and elevated ROS production in both systems only at high concentrations. α-bisabolol (chamomile) showed no immediate effects on all end points at low concentrations, but several disturbances occurred at high concentrations. Eugenol (holy basil) at moderate to high concentrations, significantly decreased contractility, cell activity and protein content. The diabetic formula used showed an increase in DNA damage and a decline in cell migration in mouse embryonic stem cells. Molecular endpoints indicate a role for reactive oxygen species and changes in cell membrane proteins. To summarise, these data indicate that some herbal remedies used in the first trimester of pregnancy might not be safe for fetal development. Also care needs to be taken to ensure good glycaemic control in diabetic pregnancy.